2002
DOI: 10.1188/02.onf.1455-1462
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of the Experiences of Lesbian and Heterosexual Patients With Breast Cancer

Abstract: Study findings may help improve healthcare services for lesbians with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 18 publications
2
58
0
1
Order By: Relevance
“…Along with the development of the concept of holism, SHC was included as a basic component of nursing care as well, while in nursing research and education remarkable advances were recorded: models for the assessment of cancer patients' sexuality were developed and, lately, promising intervention projects were implemented for the provision of intensive SHC [2,4,13,24,34,35,45,58,59,62,67,71,72,74,75,91,93,103,106,124,125]. Since then, several studies have concluded with some important findings: the majority of cancer patients report sexual issues to be a priority [79,80]; concerns about sexual function are augmented and sustained after the experience of cancer [97]; a remarkable number of individuals are willing to discuss sexual concerns with their health providers [110], while trained oncology nurses are considered to be explicitly helpful with patients' sexual problems [4,75].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the development of the concept of holism, SHC was included as a basic component of nursing care as well, while in nursing research and education remarkable advances were recorded: models for the assessment of cancer patients' sexuality were developed and, lately, promising intervention projects were implemented for the provision of intensive SHC [2,4,13,24,34,35,45,58,59,62,67,71,72,74,75,91,93,103,106,124,125]. Since then, several studies have concluded with some important findings: the majority of cancer patients report sexual issues to be a priority [79,80]; concerns about sexual function are augmented and sustained after the experience of cancer [97]; a remarkable number of individuals are willing to discuss sexual concerns with their health providers [110], while trained oncology nurses are considered to be explicitly helpful with patients' sexual problems [4,75].…”
Section: Introductionmentioning
confidence: 99%
“…This neglect is particularly important in light of research finding that, among sexual minority women with breast cancer, openness about sexual orientation was associated with lower levels of emotional distress, although discordance in level of disclosure between patients and their partners was associated with greater distress (Boehmer, Freund, & Linde, 2005). Moreover, Matthews, Peterman, Delaney, Menard, and Brandenburg's (2002) focus group study comparing lesbian and heterosexual breast cancer survivors found that lesbian survivors reported less satisfaction with their treatment compared to heterosexual women.…”
Section: Sexual Minority Women and Breast Cancer Researchmentioning
confidence: 99%
“…Additionally, members of the lesbian community have been shown to require unique forms of social support after diagnosis with breast cancer (Boehmer, Freund, & Linde, 2005). Further, this population reports a lower satisfaction with the care they receive from breast cancer providers (Matthews, Peterman, Delaney, Menard, & Brandenburg, 2002). These findings elucidate the need for research related to end-of-life communication with single and lesbian patient populations.…”
Section: Discussionmentioning
confidence: 94%